G586(P) Quality Improvement Project: Preventing hypothermia in Neonates in a tertiary neonatal unit. (27th April 2016) - Shaw, A; Jones, K; Farooq, S; Ashton, C; Stevens, R; Hopley, C; Miall, L
Abstract : Aim: This project aimed to reduce the number of babies admitted to a tertiary neonatal unit with hypothermia through development of improvement interventions. Our benchmark was for 90% of babies to have an admission temperature within the normal range (as per our local guideline, 36.5–37.5°C). Background: Thermoregulation is a critical aspect of newborn care. The close association of hypothermia with increased morbidity and mortality has been well documented. Consequences include hypothermia, respiratory distress and development of metabolic acidosis. A recent audit revealed hypothermia was present in 23% patients on admission. The majority of these were small for gestation term babies. Causes included prolonged delivery/resuscitation, deviation from thermoregulation guidelines and delay in checking initial temperature. A working group was developed to instigate changes in practice. Methods: The project was conducted from November 2014 to June 2015. PDSA (Plan-Do-Study-Act) methodology was followed. It was co-ordinated by the consultant lead and included members of the multi-disciplinary team (doctors, neonatal nurses, midwives). All gestational ages were targeted. Axillary thermometers were used to take admission temperature and BadgerNet was utilised to capture this. Pre-intervention information was collected over a 3 month period. Changes were subsequently implemented on a monthly basis; producing educational posters, addressing skin-to-skin practice, use of hats and temperature measurement before transfer. Educational posters were placed in each delivery room and by the resuscitaire in theatre. They aimed to prompt staff about the importance of skin-to-skin and drying babies with a warm towel. Skin-to-skin guidance was updated to incorporate this and training given to maternity staff. Use of hats were encouraged for both preterm and term babies. Temperatures were recorded on delivery suite before transfer to the neonatal unit. This permitted an opportunity to address any temperatures which were outside the normal range. We anticipated an exponential increase with each subsequent intervention. Several midwives were identified as champions for the project. Exclusion criteria included babies undergoing cooling, outborn babies and admissions from the postnatal ward. Results were regularly updated and run charts disseminated throughout the department. Results: Pre-intervention analysis showed a cumulative baseline of 65.9% with acceptable admission temperature (see chart). Each subsequent intervention raised the cumulative percentage further. The cumulative average by week 33 was 70.7%. Checking the temperature prior to transfer had the greatest single impact with 80% admissions within range for that monthly period. Despite the overall upward trend there was still inter-variability between individual temperatures. The lowest admission temperature was 34.2°C. The highest was 40°C. Conclusion: This project has significantly reduced the number of hypothermic babies admitted to the neonatal unit. Subsequently, associated complications have decreased. The local unit is now exceeding national averages. Recording temperature 15 min after birth had the most significant effect. Large variation still exists on an individual level. Further improvement is paramount in order to meet our target range. This project facilitated understanding of PDSA methodology and the value of quality improvement in the workplace. Lessons learnt included the importance of reiterating information, use of motivated champions and regular feedback to highlight success. The main barrier to improvement was changing established practices/attitudes. Recommendations: Staff education on importance of thermoregulation in all newborns → to keep all babies warm. To continue with interventions previously deployed at local level. Continual improvement by analysing further change → temperature in delivery suite, transportation policy, postponing weighing babies and assessing adoption of new sterile bags for preterm delivery. Dissemination of results to wider team → update provided to obstetrics, discussed in department newsletter, practice highlighted at regional conference. Establishing a CQUIN.